Legal Protection on Intellectual Property Rights in the Development of Creative Economy in Mamuju Regency - Suryansyah Suryansyah (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
Protection of legal intellectual property rights is the main pillar for businesses, especially those engaged in the creative economy business. The role of law can provide guarantees and legal certainty in creating a good economic climate and increasing people’s income derived from the results of the work of creativity, ideas and creativity. The creative economy becomes a strategic issue as a government effort in developing the regional economy, creating a climate of creation and innovation and leading to improving people’s welfare. The development of creative economic ventures in Mamuju Regency, West Sulawesi Province must be supported by a set of regional regulations, specifically those that regulate the protection of intellectual property rights of creative economy entrepreneurs. So that business people get protection, justice, benefit and legal certainty related to the work of copyright and innovation products owned. This study aims to examine the regional regulations of Mamuju Regency about the economy, especially the protection of intellectual property rights for creative economic business actors and identify the potential of the creative economy. Data is collected through literature studies to trace data through regional regulation documents. The processed data from descriptive analysis is used as a basis for consideration and review of economic law. The results of this study are in the form of sources of economic law material and manuscripts of academic considerations, where the local government and the public can find out the legal position in the protection of intellectual property rights of creative economy entrepreneurs in Mamuju Regency.